ANALISIS PERBEDAAN PENGELOLAAN PEMUNGUTAN PPH 21 APARATUR SIPIL NEGARA (ASN) SEBELUM DAN SESUDAH IMPLEMENTASI PERATURAN DIREKTORAT JENDERAL PAJAK No. 32/PJ/2017 (Studi Kasus di Kantor Pemerintah Daerah Kabupaten Bulukumba) - Muhammad Taufik Rahman; Muhammad Hidayat; Andi Djalante (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2020)
This study aims to (1) identify and analyze the differences in the management of withholding income tax 21 tax cutters before and after the implementation of Tax Directorate Regulation No. 32 / PJ / 2017 at the Bulukumba District Government Office. (2) To identify and analyze implementation barriers before and after the Directorate General of Taxation Regulation Number 32 / PJ / 2017 and their impact on the quality of tax reporting at the Bulukumba Regency Regional Government Office. The research was conducted at the Bulukumba Regency Government Office by taking 58 samples, namely treasurers and assistant treasurer staff. When the research was conducted from July to August 2020. The results showed (1) there was no difference in the deduction of Article 21 PPh tax for ASN at the Bulukumba Regency Regional Government Office in 2015-2016 and 2018-2019 before and after the implementation of the Directorate Regulation General Tax No. 32 / PJ / 2017 where the Bulukumba Regency Government Office has carried out procedures for calculating and deducting PPh 21 on the salaries of State Civil Servants (ASN) in accordance with the Directorate General of Taxes Regulation Number 32 / PJ / 2017. (2) There are no obstacles in the implementation of the Directorate General of Taxes Regulation Number 32 / PJ / 2017 and the impact on the quality of tax reporting because all of the tax deductions have been deducted beforehand when ASN at the Bulukumba Regency Regional Government Office receives a regular salary. Until now, there is no or no information regarding civil servants who are not aware of paying taxes